Pelestarian Dan Penyelamatan Koleksi (Studi Kasus Pada Perpustakaan Ali Hasjmy Banda Aceh) - Rahmi, Nurul (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
Preservation is a way of protecting library materials in the library. This study aims to determine the preservation and rescue of collections (a case study at the Ali Hasjmy library in Banda Aceh). The research method used is descriptive qualitative research. Data collection techniques used by observation, interviews, and documentation. Researchers conducted interviews with 1 library manager. The resulting data is then analyzed into narratives and paragraphs. The results showed that the Ali Hasjmy library carried out preservation by cleaning the library and there were several manuscripts that had been restored. However, special subscriptions are still needed so that the collections contained in the Ali Hasjmy library maintain their informational value. Some of the collections contained in Ali Hasjmy's library include: collections of manuscripts, ceramics, weapons, Acehnese saga, Acehnese clothing. Hopefully this research can provide benefits for Ali Hasjmy's library and the government will also look at the library. In addition, cooperation with the Aceh Museum and the Aceh Cultural Value Preservation Center (BPNB) is also provided so that many people can enjoy and use Aceh's cultural values and treasures.